(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine the expression of p-STAT3 in gastric cancer tissues and evaluate its association with selected laboratory parameters in the study population. Subjects and methods: A descriptive analytical study was conducted on 68 patients with gastric adenocarcinoma. p-STAT3 expression was assessed by immunohistochemistry. Laboratory parameters were compared between groups using the Mann-Whitney U test. Results: The rate of positive p-STAT3 expression was 32.35%. The p-STAT3-positive group had significantly lower hemoglobin levels than the p-STAT3-negative group [119.5 g/l (103.75-139.25) vs. 136.0 g/l (125.75-148.25); p = 0.020] and lower hematocrit values [0.36 l/l (0.31-0.41) vs. 0.41 l/l (0.37-0.44); p = 0.019]. Red blood cell counts tended to be lower in the p-STAT3-positive group, although the difference was not statistically significant (p = 0.082). No significant differences were observed in other biochemical parameters (p > 0.05). Conclusions: p-STAT3 was expressed in 32.35% of gastric cancer cases. Positive p-STAT3 expression was associated with lower hemoglobin and hematocrit levels in patients with gastric cancer.